Identification and expression analysis of myo-inositol oxygenase gene family in Brassica napus L. - CHEN Shubing; XU Zishu; HUANG Qian; ZHANG Hui; ZHANG Kangni; DUAN Yi; SUN Yue’e; ZHOU Weijun; XU Ling (浙江大学学报. 农业与生命科学版)
Myo-inositol oxygenase (MIOX) catalyzes the conversion of myo-inositol to glucuronic acid and plays an important role in response to biotic and abiotic stresses. In this study, the genome-wide identification and expression pattern analysis of the MIOX family gene in Brassica napus L. (BnMIOX) were conducted. The results showed that the BnMIOX family included 12 members distributed across nine chromosomes. According to the characteristics of MIOX gene domain, the phylogenetic tree of B. napus, Arabidopsisthaliana, B. rapa and B. oleracea could be divided into subfamilies Ⅰ, Ⅱ and Ⅲ. No tandem repeat gene pairs were found in the collinearity analysis, and all of them were large segment replication genes, demonstrating that segmental duplication and whole-genome duplication were the main driving forces for the MIOX gene family amplification in B. napus. The transcriptomic data indicated that BnMIOX genes showed different temporal and spatial expression patterns in different tissues and different growth and development processes. Expression profiles under different stresses demonstrated that the expression of BnMIOX1 gene was obviously induced under drought and salt stresses, while BnMIOX1, BnMIOX2, and BnMIOX9 genes had significant responses to drought, salt, abscisic acid (ABA), and cold stresses. The results of the protein interaction network analysis further showed that the BnMIOX interacted with proteins including GLCAK, PIS1, VTC2, VTC4, and PDF2.1, implying that BnMIOX genes play key roles in improving the resistance of B. napus. This study provides an important basis for further investigation of the function of BnMIOX genes.